Randomized placebo-controlled trial of high-dose prenatal third-trimester vitamin D3 supplementation in Bangladesh: the AViDD trial - Roth, Daniel E (BioMed Central, 2013)
BACKGROUND: Antenatal vitamin D status may be associated with the risk of adverse pregnancy and neonatal outcomes; however, the benefits of vitamin D supplementation during pregnancy remain unknown. METHODS: We conducted a double-blind placebo-controlled randomized trial to evaluate the effect of high-dose prenatal 3(rd) trimester vitamin D3 supplementation on maternal and neonatal (cord blood) serum 25-hydroxyvitamin D (25(OH)D) concentration (primary biochemical efficacy outcome) and maternal serum calcium concentration (primary safety measure). Eligibility criteria were pregnant women aged 18 to <35 years, at 26 to 29 weeks gestation, and residing in Dhaka, Bangladesh. 160 women were randomized by 1:1 allocation to one of two parallel intervention groups; placebo (n = 80) or 35,000 IU/week of vitamin D3 (n = 80) until delivery. All participants, study personnel and study investigators were blind to treatment allocation. RESULTS: Mean maternal 25(OH)D concentration was similar in the vitamin D and placebo groups at baseline (45 vs. 44 nmol/L; p = 0.66), but was significantly higher in the vitamin D group vs. placebo group among mothers at delivery (134 vs. 38 nmol/L; p < 0.001) and newborns (cord blood: 103 vs. 39; p < 0.001). In the vitamin D group, 95% of neonates and 100% of mothers attained 25(OH)D >50 nmol/L, versus 21% mothers and 19% of neonates in the placebo group. No participants met criteria for hypercalcemia, there were no known supplement-related adverse events, and major pregnancy outcomes were similar between groups. CONCLUSIONS: Antenatal 3(rd)-trimester vitamin D3 supplementation (35,000 IU/week) significantly raised maternal and cord serum 25(OH)D concentrations above 50 nmol/L in almost all participants without inducing hypercalcemia or other observed safety concerns. Doses up to 35,000 IU/week may be cautiously used in further research aimed at establishing the clinical effects and safety of vitamin D3 supplementation in pregnancy. TRIAL REGISTRATION: This trial was registered at ClinicalTrials.gov (NCT01126528).